Afterslip, viscoelastic relaxation, poroelastic rebound: A possible mechanism in the short and long term postseismic deformation following the 2011 Tohoku earthquake - Panuntun, Hidayat (2017)
Postseismic deformation of the Tohoku earthquake has been investigated by Ozawa et al. (2011), Wang et al. (2012), Diao et al. (2013), Sun et al. (2014), Perfettini and Avouac (2014), Shirzaei et al. (2014), Silverii et al. (2014), and Yamagiwa et al. (2015). Of these studies, Diao et al. (2013) investigated rheological model inferred from postseismic deformation of the Tohoku earthquake using 1.5 years GPS data following the mainshock. Because reliable investigation of the viscosity and its transient behavior require observation with longer time period, we build postseismic deformation model of the Tohoku earthquake using longer GPS data than that of used by previous studies and estimated the inferred rheological model. In addition, we also evaluate the possibility of the poroelastic relaxation signal due to the Tohoku earthquake.